A fixed point theorem for nonself nonlinear contractions in length spaces - Reich, Simeon; Zaslavski, Alexander J. (Topological Methods in Nonlinear Analysis, 2024)
In 1988 N.A. Assad showed that a nonself nonlinear contraction taking a closed subset of a complete metrically convex space into the space so that the boundary of this subset is mapped back into the subset itself has a unique fixed point. In the present paper we extend this result by replacing the complete metrically convex space with a complete metric space which is a length space.